Circulating lipid levels and risk of coronary artery disease in a large group of patients undergoing coronary angiography - Deeb, Mary E. (2015)
A main underlying pathology of coronary artery disease is the deposition of cholesterol in the arteries supplying blood to the heart that leads to stenosis and myocardial infarction. We tested if dyslipidemia is a risk factor for coronary artery disease in the Lebanese population, and studied the role of the total cholesterol/HDL cholesterol (TC/HDL-C) ratio as a biological marker of coronary artery disease. We recruited 6,180 Lebanese patients undergoing cardiac catheterization. We conducted a cross-sectional association study between TC/HDL-C ratio and the number and type of vessels occluded in catheterized patients by controlling for confounding effects. The TC/HDL-C ratio ≥4 significantly predicts ≥50 % stenosis in all vessels individually with the odds ratio (OR) ranging from 1.22 to 1.92. The OR increased with increasing number of ≥50 % stenotic vessels (1.39 for 2 vessels and 1.64 for 3–4 vessels), as did risk due to diabetes, CAD family history, gender, and age. The younger than average age of onset subgroup shows a pronounced increase in risk for occlusion of the left main coronary artery due to TC/HDL-C ≥4 (OR 3.26). In conclusion, low levels of HDL-cholesterol and high levels TC/HDL-C ratio are strong biological markers of disease occurrence and severity in the Lebanese population.